International Business Mergers and Acquisitions in Japan - Bebenroth, Ralf (Springer, 2015)
This book is one of the very few published investigations of international business in a Japanese context, based on an up-to-date overview of the Japanese mergers and acquisitions (M&A) market in particular. The author explicates recent developments in Japanese business and shows how Japanese firms drastically change to reach out to become more globalized. The book can serve as a foundation in a teaching module for any Japan-related class in international business. Specifically, this publication reveals the inner workings of the Japanese business system. M&A activities covered here include those of foreign firms in Japan as well as Japanese firms investing domestically and in cross-border ventures. Illustrated by carefully chosen examples and supported by extensive data analyses, this book is highly recommended to readers who seek an in-depth understanding of the Japanese M&A market. The volume is enriched by case studies that explicitly illustrate the objectives of specific firms and how they successfully manage their M&A. The author brings to this work his 14 years of experience in Japan and has relied not only on English literature but also on original Japanese sources in creating this highly valuable contribution to the field.